Metode Debat dalam Pembelajaran: Sebuah Upaya Peningkatan Kemampuan Berpikir Kritis Mahasiswa - Nasir, Muhammad; Fendi, Hasri; Indriyani, Vivi (Jurnal Bahasa dan Sastra, 2024)
The ability to think critically is an important skill today, especially in facing the era of development of knowledge and technology in the 21st century. With this ability, students can analyze the truth of information both heard and read. However, this skill is still in a low level category so efforts are needed to improve it. One effort is to use innovative learning methods that can improve students' critical skills, namely the debate method. The aim of this research is to evaluate the level of critical thinking skills of BSA Study Program students, test the effectiveness of the debate, and provide academic suggestions for study programs and lecturers to improve the quality of learning that focuses on developing BSA students' critical thinking skills. This research method uses an experimental method. The subject of this research is the BSA Study Program, Faculty of Adab and Humanities, UIN Imam Bonjol Padang. This research data consists of two things, namely students' skills during debate and students' critical thinking abilities which were tested through tests. This research concludes that the debate method is effective in improving students' critical thinking skills and students' ability to build arguments, which can be achieved through structured and theory-based exercises. These findings can be widely used to train students' critical thinking skills and as a learning strategy in class by lecturers.